Multisystem comorbidities in classic Rett syndrome: a scoping review. Issue 1 (22nd September 2020) - Fu, Cary; Armstrong, Dallas; Marsh, Eric; Lieberman, David; Motil, Kathleen; Witt, Rochelle; Standridge, Shannon; Lane, Jane; Dinkel, Tristen; Jones, Mary; Hale, Katie; Suter, Bernhard; et al.
Abstract : Background: Rett syndrome (RTT) is a severe, progressive neurodevelopmental disorder with multisystem comorbidities that evolve across a patient's lifespan requiring attentive coordination of subspecialty care by primary care providers. A comprehensive, up-to-date synthesis of medical comorbidities in RTT would aid care coordination and anticipatory guidance efforts by healthcare providers. Our objective was to review and summarise published evidence regarding prevalence of RTT medical comorbidities across all relevant organ systems. Methods: Search of PubMed from January 2000 to July 2019 was performed using the search terms (Rett and MECP2 AND patient) OR (Rett and MECP2 AND cohort). Articles reporting the prevalence of clinical findings in RTT were assessed with respect to the size and nature of the cohorts interrogated and their relevance to clinical care. Results: After review of over 800 records, the multisystem comorbidities of RTT were summarised quantitatively from 18 records comprising both retrospective and prospective cohorts (31–983 subjects). Neurological comorbidities had the highest prevalence, occurring in nearly all individuals with gastrointestinal and orthopaedic concerns almost as prevalent as neurological. With the exception of low bone mineral content which was relatively common, endocrine comorbidities were seen in only around one-third of patients. Although more prevalent compared with the general population, cardiac conduction abnormalities were the least common comorbidity in RTT. Conclusions: Effective care coordination for RTT requires knowledge of and attention to multiple comorbidities across multiple unrelated organ systems. Many issues common to RTT can potentially be managed by a primary care provider but the need for sub-specialist referral can be anticipated. Since the median life expectancy extends into the sixth decade with evolving subspecialty requirements throughout this time, paediatric providers may be tasked with continued coordination of these comorbidities or transitioning to adult medicine and specialists with experience managing individuals with complex medical needs.